Predictors of postoperative bleeding in children undergoing cardiopulmonary bypass: A preliminary Italian study. Issue 153 (May 2017) - Spiezia, Luca; Di Gregorio, Guido; Campello, Elena; Maggiolo, Sara; Bortolussi, Giacomo; Stellin, Giovanni; Simioni, Paolo; Vida, Vladimiro
Abstract: Background: Several characteristics such as demographics, pre-existing conditions, surgical procedure, perioperative coagulopathy may predispose children undergoing cardiopulmonary bypass (CPB) to bleeding complications. As yet, studies on risk factors for postoperative bleeding have brought mixed results. The purpose of our study was therefore to retrospectively evaluate the parameters able to predict postoperative bleeding in a group of consecutive children undergoing cardiac surgery involving CPB. Methods: We collected demographic and perioperative laboratory data, as well as intraoperative transfusion requirements and blood loss during the first 24 h after surgery in a group of consecutive children (aged ≥ 1 month) scheduled for cardiac surgery with CPB at Padua University Hospital between June 2014 and April 2015. Cases were patients who experienced a 24-h postoperative blood loss ≥ 80th percentile. Univariate and multivariate logistic regression analyses were performed to determine the independent parameters associated with a high 24-h postoperative chest tube drainage volume. Results: Eighty-three children (M:F 38:45; age range 1–168 months) were enrolled. Age < 7.7 months (p 0.015), postoperative platelets < 109 × 10 9 /L (p 0.003) and postoperative D-dimer ≥ 2350 μg/L (p 0.007) were the variables most significantly and independently associated with excessive 24-h postoperative blood loss. Conclusions: Although preliminary, our study identified younger age, lower postoperative platelet count and higher D-dimer plasma levels as possible risk factors for postoperative bleeding. As for coagulation parameters, our results suggested consumptive coagulopathy might cause a strong predisposition to postoperative bleeding in children. Large-scale prospective studies would provide insight into the early diagnosis and treatment of CPB-related coagulopathies. Highlights: Children undergoing cardiopulmonary bypass (CBP) surgery have an increased bleeding risk. Early identification of patients at higher risk can prevent bleeding complications. Predisposing factors were found to be younger age, low platelet count and increased D-dimer.